Numerical Study on the Use of Alternating Injection Hydraulic Fracturing Technology to Optimize the Interaction Between Hydraulic Fracture and Natural Fracture - Yang, Yang; Xie, Lingzhi; He, Bo; Zhao, Peng (Frontiers in Earth Science, 2022)
Hydraulic fracturing is a key technology for shale gas production. Activating the natural fracture (NF) system in shale reservoirs and forming a complex fracture network can greatly improve the effect of fracturing. The effect of fracturing is mainly influenced by geological factors and operational parameters of a reservoir. Effectively reforming a reservoir under unfavourable geological conditions and maximizing the activation of NFs in the reservoir can substantially increase its reformed volume and the production of shale gas. Alternating fluid injection (AFI) fracturing technologies using multiple fracturing fluids with different viscosities can activate closed NFs while retaining the high conductivity of the principal fracture to achieve a larger stimulated reservoir volume (SRV). In this paper, a fluid mechanical coupling finite element model (FEM) of a reservoir is established, and AFI fracturing technology is numerically simulated using the continuum method. In addition, the fracture propagation stage and path propagation for AFI technology are discussed. The results show that AFI fracturing technology can form principal fractures with high conductivity and activate NFs in a reservoir to form comparatively complex fracture propagation paths.